Penilaian AHP Jalur Hijau Koridor Transjakarta 8 DKI Jakarta Berdasarkan Fungsi Ekologis Vegetasi - Lasta Musfira; Nizar Nasrullah; Bambang Sulistyantara (Jurnal Ilmu Pertanian Indonesia, 2024)
Greenbelt and green infrastructure are still very limited in Jakarta. Transjakarta Corridor 8 Harmoni - Lebak Bulus covers Central Jakarta, West Jakarta, and South Jakarta which are government centers and densely populated settlements. The high activity in the area causes an increase in transportation flows and greenhouse gas emissions. The transportation sector is the highest contributor to CO2e emissions in the capital city, thus reducing environmental quality, especially the greenbelt in Transjakarta Corridor 8. The assessment of ecological functions in this study consists of 7 variables, namely noise reduction, pollution reduction, air humidity, view control, glare control, direction and accident prevention. The research location is divided into 5 segments with the analysis method used, namely the assessment of ecological function aspects and the formulation of recommendations based on Hierarchical Process Analysis. The results of the assessment on ecological functions with noise-canceling variables were (Polyalthia longifolia) Glodongan Tiang, (Casuarina sp.) Spruce, (Acacia auriculiformis) Acacia, and (Archontophoenix alexandrae) Alexander Palm. The results of the pollution reduction assessment of each segment are dominated by vegetation types (Mangifera indica) Mango, (Polyalthia longifolia) Glodongan Tiang, (Carbera odollam) Bintaro. Based on the results of the questionnaire, the AHP assessment weight was obtained. The combined AHP results show the highest priority scale for the evaluation recommendations of this research is Pollution Reduction as the most important variable with a weight of 0.348, the second rank is Accident Reducer with a weight of 0.300, the third rank is Glare Control with a weight of 0.150. The combined results of 3 experts produce a consistency ratio value of 0.05, the consistency ratio value of 0.05 is smaller than 0.10 so it can be said to have met the consistent requirements. Keywords: analytical hierarchy process, emission, roadside greenbelt